DEVICES, SYSTEMS, AND METHODS OF GENERATING AND PROVIDING A TARGET TOPOGRAPHIC MAP FOR FINISHING A PHOTOMASK BLANK SUBJECT TO FUNCTIONAL REQUIREMENTS ON FLATNESS - ARONSTEIN, David L; BALLMAN, Katherine Nicole; LEE, Christopher Alan (2022)
Devices, systems, and methods of generating and providing a target topographic map for finishing a photomask blank are disclosed. A method includes receiving topographic data corresponding to an uncompleted photomask blank, receiving functional specifications for flatness of an acceptable photomask blank, and generating the target topographic map for first and/or second major surfaces of the blank, which provides instructions for removing material from the first and/or second major surfaces such that the first and second major surfaces achieve a flatness that passes each functional specification. The amount of material removed reflects a reduction in material necessary to pass the functional specifications. The method further includes transmitting the target topographic map to the finishing device to utilize a finishing technique to implement changes to the photomask blank according to the target topographic map by removing the material from the photomask blank to achieve a photomask blank that passes the functional specifications.